MEDIATING EFFECT OF SUSTAINABILITY TO SUPPLY CHAIN RESILIENCE AND PERFORMANCE AMONG CONSTRUCTION COMPANIES IN BEIJING, CHINA - ZHU, MEIJU (Pacific International Journal, 2024)
This study investigates the integration of sustainable supply chain management (SSCM) principles and supply chain resilience (SCR) strategies in the context of the construction industry in Beijing. Sustainable practices in supply chains are increasingly recognized as critical for enhancing resilience against disruptions and improving overall performance. The research synthesizes existing literature on SSCM and SCR, highlighting theoretical foundations, empirical evidence, and frameworks. Key findings underscore the interplay between sustainability initiatives, such as resource management and environmental stewardship, and resilience factors like flexibility and redundancy. Case studies from Beijing illustrate practical applications, demonstrating how sustainable practices mitigate risks and enhance adaptability in construction supply chains. The study concludes with recommendations for future research directions and practical implications for industry stakeholders aiming to foster resilient and sustainable supply chain practices.